Enhancing Staff’s Work Motivation in Vietnamese Companies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, with the trend of globalization, with increasingly fierce competition, it isrequired that businesses that want to succeed must constantly improve their quality and improvethemselves to be able to stand firm in the market. In addition, people are being considered as aninvaluable asset, which is a fundamental factor that determines the existence and development ofan enterprise. In the context that society is gradually shifting to a knowledge-based economy, abusiness, even with rich and strong financial resources, becomes meaningless without the humanelement. Without effective employees, the organization cannot achieve its goals. Whenemployees are motivated to work, they will work very enthusiastically, passionately and that willcreate high labor productivity, contributing to the achievement of business and production goalsof the enterprise. This article analyzes in-depth the specific work motivation of staff in severalVietnamese enterprises.